2021
DOI: 10.1177/1524839921996065
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Review of Arts-Based Strategies for Addressing Pain and Substance Use Disorder During the Opioid Crisis

Abstract: In October 2017, the U.S. Department of Health & Human Services declared the opioid crisis a national public health emergency and prioritized identifying effective, evidence-based strategies for pain management and the prevention and treatment of substance use disorder (SUD). Increasingly, the arts have become more widely established and accepted as health-promoting practices in the United States and around the world. As the U.S. health care system moves toward greater integration of physical and behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This landmark review produced several findings that informed both the intention and structure of the Analgesic Museum conference. First, the NEA review found that the majority of studies conducted on pain management focused on post-operative pain (vs. persistent pain) and investigated music-based interventions (vs. museum-based interventions) (5). Second, the report called for more research on the arts' impact on persistent pain and on the social dimensions of pain (5).…”
Section: Setting the Scenementioning
confidence: 99%
See 1 more Smart Citation
“…This landmark review produced several findings that informed both the intention and structure of the Analgesic Museum conference. First, the NEA review found that the majority of studies conducted on pain management focused on post-operative pain (vs. persistent pain) and investigated music-based interventions (vs. museum-based interventions) (5). Second, the report called for more research on the arts' impact on persistent pain and on the social dimensions of pain (5).…”
Section: Setting the Scenementioning
confidence: 99%
“…First, the NEA review found that the majority of studies conducted on pain management focused on post-operative pain (vs. persistent pain) and investigated music-based interventions (vs. museum-based interventions) (5). Second, the report called for more research on the arts' impact on persistent pain and on the social dimensions of pain (5). The conference responds to these findings by not only highlighting projects that specifically examine the role of non-music-based arts programming to address persistent pain, but through the identification of topic areas-Exhibition development; Arts experiences and practices; Research and creative scholarship-that will foster more research and programming in these gap areas of study and practice.…”
Section: Setting the Scenementioning
confidence: 99%